MEWUJUDKAN MULTIKULTURALISME DI INDONESIA MELALUI TOLERANSI - Novi Dwi Gitawati (Asosiasi Dosen Muda Indonesia, 2022)
Indonesia is a nation with diverse etnics, cultures and social groups. Instead of being seen as an obstacle in advancing the nation, the social diversity that has existed since the birth of this country should be seen as an advantage that must be realized and maintained with the spirit of multiculturalism for the sake of our nation development. Based on this view, this paper tries to discuss multiculturalism and steps that can be taken by the Indonesian people to make it happen. Efforts to realize the hopes of multiculturalism in Indonesia can be realized, one of which is by promoting toleration between ethnic groups, cultures, and existing social groups. Based on Forst's concept of toleration, multiculturalism in Indonesia is expected to happen through toleration that occurs in two of Forst’s four conceptions of toleration, namely: respect conception and esteem conception.